2007
DOI: 10.1063/1.2771158
|View full text |Cite
|
Sign up to set email alerts
|

Electronic states of neutral and cationic bis(benzene) titanium and vanadium sandwich complexes studied by pulsed field ionization electron spectroscopy

Abstract: Ti- and V-bz2 (bz=C6H6) sandwich complexes have been prepared in a laser-ablation cluster beam source and studied by pulsed field ionization-zero electron kinetic energy photoelectron spectroscopy and theoretical calculations. The ground electronic states of the neutral Ti- and V-bz2 complexes are determined to be 1A1g and 2A1g, and their ionization energies are measured to be 5.732+/-0.001 and 5.784+/-0.002 eV, respectively. These neutral complexes have eta6 binding and are in an eclipsed D6h configuration wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 40 publications
(57 reference statements)
0
30
0
Order By: Relevance
“…The full width at half maximum of this peak is about 12 cm −1 and the broad linewidth is due to unresolved rovibronic transitions. 28,30,31,34 Measurements with a heavy carrier gas would reduce the linewidth by decreasing rotational temperatures of the neutral molecules. Unfortunately, experiments with Ar or Ar/He carriers were unsuccessful due to very weak signals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full width at half maximum of this peak is about 12 cm −1 and the broad linewidth is due to unresolved rovibronic transitions. 28,30,31,34 Measurements with a heavy carrier gas would reduce the linewidth by decreasing rotational temperatures of the neutral molecules. Unfortunately, experiments with Ar or Ar/He carriers were unsuccessful due to very weak signals.…”
Section: Resultsmentioning
confidence: 99%
“…29 The B3LYP ͑Becke's three parameter hybrid functional with the correlation functional of Lee, Yang, and Parr͒ functional was selected because previous studies have shown that this method yielded good agreement with experimental ZEKE spectra of metal-aromatic complexes. 28,30,31 In these calculations, the all electron 6-311+ G͑d , p͒ basis was used for all atoms.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…Recently, Sohnlein et al 42 have performed ZEKE-PES measurements on bis-benzene complexes of titanium and vanadium, which provide information on the energetics of the occupied orbitals, but not of the unoccupied ones, and hence they cannot be compared with the optical spectra. On the other hand, Zheng et al 43 have performed anion photoelectron measurements on ͑Ti n Bz m ͒ − .…”
Section: -3mentioning
confidence: 99%
“…Kaya group [5][6][7] systematically studied the properties of 3d transition metal-benzene complexes M m (benzene) n (M = Sc, Ti, V, Cr, Mn, Fe, Co, Ni) in the gas phase, including their structures, photodissociation processes, bonding energies and ionization energies. But the reported experimental [12][13][14][15] and theoretical [19,[22][23][24][25][26][27][28][29] studies are mainly on the transition metal-benzene cationic and neutral complexes. However, the experimental and theoretical studies of metal-benzene anion complexes are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many experimental [5][6][7][8][9][10][11][12][13][14][15] and theoretical [16][17][18][19][20][21][22][23][24][25][26][27][28][29] investigations on the interaction of metal clusters with benzene in gas phase were extensively reported. Kaya group [5][6][7] systematically studied the properties of 3d transition metal-benzene complexes M m (benzene) n (M = Sc, Ti, V, Cr, Mn, Fe, Co, Ni) in the gas phase, including their structures, photodissociation processes, bonding energies and ionization energies.…”
Section: Introductionmentioning
confidence: 99%